Patterns of Vowel Epenthesis in Nigerian Spoken English - Adedeji , Kofoworola A. (Corpus Intellectual, 2024)
Vowel epenthesis is a regular speech reduction phenomenon across both formal and casual speech styles among English native speakers. However, in non-native speaker environments such as Nigeria, this phonological process is often categorized as a mispronunciation, a deviant interference features symbolic of basilectal-level spoken English. This study examines the patterns and motivations of epenthesizing in both lento and allegro naturally-occurring English spoken by Nigerians, analyses utterance tokens within a theory of conversational phonology and concludes that in a similar vein with other speech reduction processes, Nigerian L2 vowel epenthesis is an attempt at achieving a more natural phonology. Phonotactics-dependent and metrical-dependent vowel epenthesis were identified as major patterns of this process, thereby providing support for the argument that this speech phenomenon is an authentic part of the Nigerian spoken English phonological system and not merely a deviant, interference-induced mispronunciation.